TECHNO-ECONOMIC COMPARATIVE STUDY OF VERY LOW HEAD HYDRO POWER: CASE STUDY IN BINTAR VILLAGE, NUNUKAN, EAST KALIMANTAN - Subekti, Ridwan Arief; Irasari, Pudji (LIPI Press, 2014)
This paper discusses techno-economic comparative study of very low head hydro power (VLHHP) between the penstock and non-penstock systems. The selected location is river current in the Bintar Village, Nunukan, EastKalimantan. The technical analysis is performed to determine the generated potential power, the type of components used and the investment cost per kW needed. The economic analysis is then conducted by implementing IRR and NPV methods to find out whether the project is economically feasible to be executed. The technical analysis results exhibit that the generated power using penstock system is higher than that of using non-penstock system; that is, 5.70 kW. The power of non-penstock system of 3.336 kW could be attained by applying modular system comprised by 4 units of propeller turbines installed in parallel. The economic analysis shows that the penstock system requires higher investment cost that is Rp58,480,272 and both systems are not feasible to be realized since they have negative NPVs. It is, therefore, recommended to fund the project through grant.